2020
DOI: 10.1097/jxx.0000000000000479
|View full text |Cite
|
Sign up to set email alerts
|

Education initiatives in cognitive debiasing to improve diagnostic accuracy in student providers: A scoping review

Abstract: Background: The high prevalence of diagnostic errors by health care providers has prompted medical educators to examine cognitive biases and debiasing strategies in an effort to prevent these errors. The National Academy of Medicine hypothesized that explicit diagnostic reasoning education of all health care professionals can improve diagnostic accuracy. Objectives: The purpose of this scoping review is to identify, analyze, and summarize the existing l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…After title and abstract screening, 69 articles underwent full-text review (1 of which) 40 was found in a systematic review. 41 Of these 69 articles, a total of 30 met all inclusion criteria. Five articles included more than one checklist.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After title and abstract screening, 69 articles underwent full-text review (1 of which) 40 was found in a systematic review. 41 Of these 69 articles, a total of 30 met all inclusion criteria. Five articles included more than one checklist.…”
Section: Resultsmentioning
confidence: 99%
“…The serial searches yielded 5761 citations, of which 2575 were duplicates and were removed. After title and abstract screening, 69 articles underwent full-text review (1 of which)40 was found in a systematic review 41. Of these 69 articles, a total of 30 met all inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, nurses in clinical practice in Japan are faced with the anxiety of having to care for several patients with diverse diseases and different clinical situations simultaneously, while consistently updating their medical knowledge [ 31 ]. NPs can effectively mitigate nurses’ workload and understand that the anxiety may be influenced by the nurses’ cognitive load about medicine [ 32 ]. Nurses operate in a different work environment than physicians and have limited opportunities to gain a deeper understanding of various treatments and laboratory testing.…”
Section: Discussionmentioning
confidence: 99%
“…In their scoping review of debiasing interventions among medical students, Griffith et al (2020) identified four primary debiasing strategies: gaining increased medical knowledge or experience (seven studies); guided reflection (eight studies); self-explanation of reasoning (nine studies); and checklists to increase diagnosis considerations (seven studies). Of these four, only guided reflection showed notable success.…”
Section: Addressing Nonrational Factorsmentioning
confidence: 99%
“…Despite its 30-year history, debiasing research remains underdeveloped and hence far from conclusive. Most of what exists focusses on diagnostic errors among medical students (See Griffith et al, 2020 for an extensive review), with a few additional studies directed toward judicial sentencing (e.g. LidĂ©n et al, 2019; Stein and Drouin, 2018).…”
Section: Addressing Nonrational Factorsmentioning
confidence: 99%